2012
DOI: 10.1093/jac/dkr571
|View full text |Cite
|
Sign up to set email alerts
|

Point prevalence survey of antibiotic use in French hospitals in 2009

Abstract: The data provide directions for further interventions, such as better use of diagnostic tools, decreasing the treatment duration and the use of combinations. In addition, the survey shows that, although cumbersome, it is feasible to improve the representativeness of national data in European surveys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 21 publications
8
46
2
1
Order By: Relevance
“…This Shows a high use of antibiotics after emergence of proven or assumed bacterial infections. These results confirmed the conclusion of previous studies (Vlahović-Palcevski et al, 2007;N'diaye, 2003), but they are higher compared to the results obtained by other studies (Zarb et al, 2011;Robert et al, 2012;Toure et al, 1997). The high use of antibiotics might increase the risk of bacterial resistance to some antibiotics; however, it is important to note that the difference between the prevalence found in this study and in previous studies does not necessarily indicate that there is inappropriate use of antibiotics where prevalence is high.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This Shows a high use of antibiotics after emergence of proven or assumed bacterial infections. These results confirmed the conclusion of previous studies (Vlahović-Palcevski et al, 2007;N'diaye, 2003), but they are higher compared to the results obtained by other studies (Zarb et al, 2011;Robert et al, 2012;Toure et al, 1997). The high use of antibiotics might increase the risk of bacterial resistance to some antibiotics; however, it is important to note that the difference between the prevalence found in this study and in previous studies does not necessarily indicate that there is inappropriate use of antibiotics where prevalence is high.…”
Section: Discussionsupporting
confidence: 91%
“…The ways of prescriptions encountered in the two health zones of Butembo city are not identical to those found in hospitals in France (Robert et al, 2012). Indeed, in France, 3rd generation cephalosporins and betalactam associated with beta-lactamase inhibitors accounted with 44%, while in the present study is ampicillin, an aminopenicillin is prescribed by 35%.…”
Section: Discussioncontrasting
confidence: 68%
“…Although compliance with appropriate timing and spectrum of AP have improved as a result of quality improvement initiatives, there remain significant deficiencies in compliance with other aspects of AP such as duration of post-operative antibiotics [3][4][5]. Given that approximately 15% of all antibiotic agents in hospitals are prescribed for surgical prophylaxis [6,7], peri-operative antibiotic prescribing patterns can be a major driver of some emerging infections (such as C. difficile) [8,9] and selection of antibiotic resistance, thus increasing healthcare costs.…”
Section: Antibiotic Prophylaxismentioning
confidence: 99%
“…Studies have shown that approximately 15% of all antibiotics in hospitals are used for SAP [6,7]. Furthermore, studies from different countries have found that SAP was used excessively and inappropriately [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%